2016
DOI: 10.1158/1940-6207.capr-15-0187
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Proinflammatory and Prosurvival Biomarkers in Oral Cancer Patients Consuming a Black Raspberry Phytochemical-Rich Troche

Abstract: Black raspberries (BRBs) demonstrate potent inhibition of aerodigestive tract carcinogenesis in animal models. However, translational clinical trials evaluating the ability of BRB phytochemicals to impact molecular biomarkers in the oral mucosa remain limited. The present phase 0 study addresses a fundamental question for oral cancer food-based prevention: Do BRB phytochemicals successfully reach the targeted oral tissues and reduce pro-inflammatory and anti-apoptotic gene expression profiles? Patients with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 64 publications
7
53
0
1
Order By: Relevance
“…Several natural compounds and micronutrients (green tea extract, curcumin, resveratrol, broccoli sprout extract, soybean extracts, vitamin E, vitamin C, lyophilized black raspberries and pomegranate juice) have been under investigation for their adequacy in oral cancer chemoprevention (6,7). These compounds contain high levels of polyphenols with anti-oxidant, anti-migratory, antiproliferative and anti-invasive effects on cancer cell properties and are proposed to restrain carcinogenesis through their action on downstream signaling pathways (8).…”
Section: Introductionmentioning
confidence: 99%
“…Several natural compounds and micronutrients (green tea extract, curcumin, resveratrol, broccoli sprout extract, soybean extracts, vitamin E, vitamin C, lyophilized black raspberries and pomegranate juice) have been under investigation for their adequacy in oral cancer chemoprevention (6,7). These compounds contain high levels of polyphenols with anti-oxidant, anti-migratory, antiproliferative and anti-invasive effects on cancer cell properties and are proposed to restrain carcinogenesis through their action on downstream signaling pathways (8).…”
Section: Introductionmentioning
confidence: 99%
“…A black raspberry ( Rubus occidentalis L.) formulation (rich in cyanidin‐3‐rutinoside and cyanidin‐3‐xylosylrutinoside) was administered to oral squamous cell carcinoma patients. Modulation of antiapoptotic and proinflammatory genes AURKA, BIRC5, EGFR, NFKB1, and PTGS2 was reported, and no adverse effect was observed (Gu et al, ; Knobloch et al, ).…”
Section: Phytochemicals As Anti‐invasion Antimetastatic and Antiangmentioning
confidence: 99%
“…Knobloch and co-workers in a phase 0 human study showed that black raspberries, when administered as freeze-dried powder supplement in oral torches to oral cancer biopsy-confirmed patients, improve gene expression profile associated with oral cancer [86]. Transcriptional biomarkers assessed showed significant improvement for the berry supplemented diet demonstrating marked reduction for the pro-inflammatory genes NFKB1, PTGS2 as well as pro-survival genes AURKA, BIRC5, EGFR all strongly associated with oral cancer risk and progression [86].…”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%
“…Transcriptional biomarkers assessed showed significant improvement for the berry supplemented diet demonstrating marked reduction for the pro-inflammatory genes NFKB1, PTGS2 as well as pro-survival genes AURKA, BIRC5, EGFR all strongly associated with oral cancer risk and progression [86]. …”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%